Manipulation of coherence property of a light source for speckle-free imaging - Thazhe Madam Rohith (2017)
For applications like Optical Coherence Tomography (OCT), Optical Coherence Microscopy (OCM), biomedical imaging which require full-field and noise-free imaging high spatial coherence of a laser source can have an adverse effect. High spatial coherence introduces the coherent artefacts such as speckle in imaging which degrades the image quality. As a result, low spatial coherence sources such as thermal sources and LEOS are still used in most full-field imaging systems, but they suffer from low brightness. While thermal sources and LEDs have low spatial coherence required for the application, they do not provide the laser-level brightness needed for high speed imaging or imaging with the intense optical scattering which is common for biomedical imaging. Brightness can be quantified by a parameter called photon degeneracy o, which is defined as the number of photons per coherence volume. In a laser source, the photon degeneracy is usually much greater than unity, for example 109 for a typical HeNe laser. In contrast, traditional low coherence sources such as thermal sources and LEOs have a degeneracy of less than 1. In recent years a number of light sources have been developed that maintain high photon degeneracy, while providing low spatial coherence such as random and degenerate lasers. However, developing new light sources with controlled properties is complicated and costly. Thus, in this project, we are aiming for a simple and low cost techniques to manipulate the spatial coherence of an existing laser to suppress the speckle formation. We studied the spatial coherence of a CW laser diodes using Young's double-slit interference and used the electroactive rotational optical diffuser in the illumination path to control and tailor the spatial coherence down to the same level as that of low coherence light sources like thermal sources and LEOs. The visibility is used as characterising parameter for spatial coherence. It is shown that the typical visibility of a slit (slit width= 2 urn and separation= 50 urn) irradiated with the CW laser diode is decreased from the value of 0.92 when no optical diffuser is used to the value of 0.52 and 0.25 when the static and moving optical diffuser (SO/MD) with diffusion angle (DA) of 1 o and 17° were used, respectively. Controlling the visibility hence the spatial coherence will be of great interest for the applications for speckle reduced imaging. It can suppress speckle formation and improve the image quality. To quantify the speckle suppression, the speckle contract (C) of the images is calculated. The ground glass is used as a scattering film and it is imaged using a CCD detector. The laser diode with no SO/MD produced a contract of about 0.76, whereas the laser diode coupled with SO/MD, DA=l o and MD, DA=17° produced a speckle contrast of about 0.24 and 0.17, respectively. The contrast produced using a white light source was negligible. We then used the same laser diode with and without SO/MD to illuminate a US Air Force resolution test chart, which was imaged in transmission mode. It is shown that a speckle-free and full-field image was obtained when the test chart is illuminated using laser diode coupled with SO/MD.